Phylogenetic Analysis of Core Melanin Synthesis Genes Provides Novel Insights Into the Molecular Basis of Albinism in Fish - Bian, Chao; Li, Ruihan; Wen, Zhengyong; Ge, Wei; Shi, Qiong (Frontiers in Genetics, 2021)
Melanin is the most prevalent pigment in animals. Its synthesis involves a series of functional genes. Particularly, teleosts have more copies of these genes related to the melanin synthesis than tetrapods. Despite the increasing number of available vertebrate genomes, a few systematically genomic studies were reported to identify and compare these core genes for the melanin synthesis. Here, we performed a comparative genomic analysis on several core genes, including tyrosinase genes (tyr, tyrp1 and tyrp2), premelanosome protein (pmel), microphthalmia-associated transcription factor (mitf), and solute carrier family 24 member 5 (slc24a5), based on 90 representative vertebrate genomes. Gene number and mutation identification suggest that loss-of-function mutations in these core genes may interact to generate an albinism phenotype. We found nonsense mutations in tyrp1a and pmelb of an albino golden-line barbel fish, in pmelb of an albino deep-sea snailfish (Pseudoliparis swirei), in slc24a5 of cave-restricted Mexican tetra (Astyanax mexicanus, cavefish population), and in mitf of a transparent icefish (Protosalanx hyalocranius). Convergent evolution may explain this phenomenon since nonsense mutations in these core genes for melanin synthesis have been identified across diverse albino fishes. These newly identified nonsense mutations and gene loss will provide molecular guidance for ornamental fish breeding, further enhancing our in-depth understanding of human skin coloration.